2017
DOI: 10.1002/jbmr.3170
|View full text |Cite
|
Sign up to set email alerts
|

Pain, Quality of Life, and Safety Outcomes of Kyphoplasty for Vertebral Compression Fractures: Report of a Task Force of the American Society for Bone and Mineral Research

Abstract: The relative efficacy and harms of balloon kyphoplasty (BK) for treating vertebral compression fractures (VCF) are uncertain. We searched multiple electronic databases to March 2016 for randomized and quasi-randomized controlled trials comparing BK with control treatment (nonsurgical management [NSM], percutaneous vertebroplasty [PV], KIVA VCF treatment system [Benvenue Medical, Inc., Santa Clara, CA, USA], vertebral body stenting, or other) in adults with VCF. Outcomes included back pain, back disability, qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…This report details the findings and recommendations of this Task Force. The work of this report builds upon that of a related ASBMR Task Force Report published in 2017 that addressed pain, quality of life, and safety outcomes associated with kyphoplasty for vertebral fractures, which is summarized in detail in Section 2, Balloon Kyphoplasty, below …”
Section: Executive Summarymentioning
confidence: 99%
“…This report details the findings and recommendations of this Task Force. The work of this report builds upon that of a related ASBMR Task Force Report published in 2017 that addressed pain, quality of life, and safety outcomes associated with kyphoplasty for vertebral fractures, which is summarized in detail in Section 2, Balloon Kyphoplasty, below …”
Section: Executive Summarymentioning
confidence: 99%
“…Several studies reported health-related QOL (HRQOL) of VCF patients because VCF could affect their HRQOL. Some studies used HRQOL as indicators by interventions such as a VP [9] or a KP [10]. The European QOL-5 dimensions, 3-level version (EQ-5D-3L) is a well-know and widely used HRQOL instrument among general instruments [11] and this instrument is also used to measure HRQOL of VCF patients widely [9,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of kyphoplasty for short-term pain relief is well documented and widely accepted 6,7 . However, the advantage of kyphoplasty over conservative therapy regarding pain relief seems to diminish over time 8 . Additionally, there is so far no study comparing the pain relief of kyphoplasty to the placebo-effect of a sham procedure 8 .…”
mentioning
confidence: 99%
“…However, the advantage of kyphoplasty over conservative therapy regarding pain relief seems to diminish over time 8 . Additionally, there is so far no study comparing the pain relief of kyphoplasty to the placebo-effect of a sham procedure 8 . Therefore, the key factors for the evaluation of the long-term benefit/risk ratio of kyphoplasty seem to be the restoration of lost vertebral body height and the correction of fracture-related spinal malposition.…”
mentioning
confidence: 99%